Prior fluid and electrolyte imbalance is associated with COVID-19 mortality - Satu Nahkuri (Nature Portfolio, 2021)
Plain language summary The clinical course of patients with COVID-19 is highly variable, with some patients barely affected and others dying. We wanted to better understand why this is the case and identify markers of COVID-19-associated mortality. To this end, we looked into the entire available medical history of more than 100,000 COVID-19 patients from the United States. We found that patients who had experienced a disturbance of electrolyte or fluid levels in the year before they contracted SARS-CoV-2 were more likely to die than patients without such a history. This observation suggests that careful monitoring and balancing of the hydration and electrolyte status during and even before a SARS-CoV-2 infection may be beneficial and possibly reduce the risk of death with COVID-19.